First point of contact physiotherapy; a qualitative study. (September 2020) - Goodwin, Rob; Moffatt, Fiona; Hendrick, Paul; Timmons, Stephen; Chadborn, Neil; Logan, Pip
Abstract: Objectives: First point of contact physiotherapy (FPCP) provides patients direct access to a physiotherapist. Literature demonstrates efficacy of FPCP. Evidence has highlighted the need for cultural shifts from both patient and professional perspectives to optimise FPCP. This study explored stakeholder perceptions of patient awareness and understanding of FPCP to better inform FPCP implementation. Design, setting, participants: A qualitative methodology utilised semi-structured interviews and focus groups. Findings from a previous realist review were used to generate a priori topic guides. Participants included patients, physiotherapists, GPs, administration staff, and commissioners. A thematic analysis was undertaken. Results: Four themes emerged that are described: level of patient awareness of the FPCP role situated against the GP as first contact practitioner, patients attain an awareness of FPCP from a variety of sources, patient understanding of physiotherapy arises from several sources and is poorly aligned with the FPCP model, characteristics and behaviours of patients influence access to FPCP services. Patient awareness and understanding was poor. Patients tended to view the GP as the default first contact practitioner. Traditional advertising approaches appeared on the whole invisible to patients and there was a reliance on signposting to facilitate patient access. Conclusion: Findings from this study can inform implementation of FPCP. Several obstacles to the optimisation of FPCP were highlighted. Improved marketing of physiotherapy generally and FPCP specifically may increase patient awareness and understanding. However, it is likely further time will be required to bring about the cultural shift in public perception required to optimise the potential of FPCP.